Multi-Response Optimization of Spark-Ignition Engine Performance Using Methanol–Butanol Ethanol Fuel Blends through Response Surface Methodology - Dwi Khusna Khusna; Gatot Setyono; Navik Kholili; Alfi Nugroho (Infotekmesin, 2026)
Improving combustion efficiency while reducing fuel consumption remains a major challenge in the development of spark-ignition (SI) engines. Oxygenated alcohol fuels have attracted considerable attention because of their potential to improve combustion quality and energy conversion efficiency. However, previous studies have mainly focused on single or binary alcohol blends, whereas comprehensive optimization of ternary methanol–butanol–ethanol (MBE) blends under different engine operating conditions remains limited. This study investigated the combined effects of MBE blend ratio (9–17 vol.%), engine speed (4000–9000 rpm), and ignition timing (15–25°CA) on SI engine performance using Response Surface Methodology based on a Face-Centered Central Composite Design (FCCD). Power, specific fuel consumption (SFC), and thermal efficiency (TE) were selected as response variables, and twenty experimental runs were conducted to develop quadratic prediction models and determine the optimum operating condition through desirability-based multi-response optimization. The developed models exhibited excellent predictive capability, with coefficients of determination (R²) exceeding 0.99 and statistically insignificant lack-of-fit values. Engine speed was identified as the most influential factor affecting all responses. The optimum operating condition was obtained at 16.21 vol.% MBE, 7015.42 rpm, and 24.31°CA, producing 6.32 kW power, 0.499 kg/kW·h SFC, 22.44% thermal efficiency, and an overall desirability of 0.973. These findings suggest that FCCD-based multi-response optimization is an effective approach for improving SI engine performance using ternary MBE fuel blends.